Emotion Processing Deficit in Euthymic Bipolar Disorder: A Potential Endophenotype. Issue 2 (March 2022) - Reddy, Preethi V.; Anandan, Saravanakumar; Rakesh, Gopalkumar; Shivakumar, Venkatarama; Joseph, Boban; Vasu, Sunil Kalmady; Agarwal, Sri Mahavir; Muralidharan, Kesavan; Venkatasubramanian, Ganesan; Narayanaswamy, Janardhanan C.
Background: Emotion processing deficits have been described in patients with bipolar disorder (BD) and are considered one of the core cognitive abnormalities in BD with endophenotype potential. However, the literature on specific impairments in emotion processing cognitive strategies (directive/cortical/higher versus intuitive/limbic/lower) in euthymic adult BD patients and healthy first-degree relatives/high-risk (HR) subjects in comparison with healthy controls (HCs) is sparse. Methods: We examined facial emotion recognition deficits (FERD) in BD ( N = 30), HR ( N = 21), and HC ( N = 30) matched for age (years), years of education, and sex using computer-administered face emotions–Matching And Labeling Task (eMALT). Results: The three groups were significantly different based on labeling accuracy scores for fear and anger (FA) (P < 0.001) and sad and disgust (SD) (P < 0.001). On post-hoc analysis, HR subjects exhibited a significant deficit in the labeling accuracy of FA facial emotions (P < 0.001) compared to HC. The BD group was found to have significant differences in all FA (P = 0.004) and SD (P = 0.003) emotion matching as well as FA (P = 0.001) and SD (P < 0.001) emotion labeling accuracy scores. Conclusions: BD in remission exhibits FERD in general, whereas specific labeling deficits of fear and anger emotions, indicating impaired directive higher order aspect of emotion processing, were demonstrated in HR subjects. This appears to be a potential endophenotype. These deficits could underlie the pathogenesis in BD, with possible frontolimbic circuitry impairment. They may have potential implications in functional recovery and prognosis of BD.